Analysis data spatial for nutrition programs: a review using geographic information system - Utomo, Bedjo; Triwiyanto, Triwiyanto; Luthfiyah, Sari; Setyobudi, Sugeng Iwan (Intelektual Pustaka Media Utama, 2024)
Nutritional problems are public health problems that are still found in developing countries, one of the prevention efforts requires nutritional data information. Geographic information systems (GIS) is an information system application that can analyze spatial data, such as population distribution, regional boundaries, and access to health centers. This study aims to examine the use of spatial data analysis with GIS in monitoring nutrition programs. The methods used in data retrieval use scientific database searches such as PubMed, Scopus, and Google Scholar as well as VOSviewer application with Keywords such as